Small-Scale Syringe and Vial-Filling Capability for Development of Robust Filling Processes, Smooth Tech Transfers, and to Resolve Manufacturing Issues: Summary of Key Learnings. - HUTTER, KEVIN; DESAI, KASHAPPA GOUD; RUSANOV, IGOR; GIDH, AARTI (BioPharm International, 2023)
Filling of syringes and vials with high-viscosity monoclonal antibodies (mAbs) or small-molecule liquid formulations is a difficult task and may present several challenges. Considerable development work may be required to develop a filling process that provides a clean fill using a small-scale or at-scale filling machine. However, performing the development work using an at-scale filling machine is neither an efficient nor cost-effective long-term option due to hectic manufacturing schedules and associated resource needs. A small-scale filling line can be used to define optimal filling process parameters, support technology transfer, and develop mitigation strategies for ongoing or potential issues with minimal disruption of normal manufacturing operation. Streamlined ways of working without requiring manufacturing-scale line time is expected to result in increased efficiency and improved portfolio progression timelines. Key learnings, case studies, and recommendations for this small-scale filler are discussed.